2017
DOI: 10.1093/ofid/ofx130
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smallpox and Bacillus Calmette-Guérin Vaccination on the Risk of Human Immunodeficiency Virus-1 Infection in Guinea-Bissau and Denmark

Abstract: BackgroundThe live smallpox and Bacillus Calmette-Guérin (BCG) vaccinations have been associated with better adult survival in both Guinea-Bissau and Denmark. In Guinea-Bissau, human immunodeficiency virus (HIV)-1 became an important cause of death after smallpox vaccination was phased out globally in 1980. We hypothesised that smallpox and BCG vaccinations were associated with a lower prevalence of HIV-1 infection, and we tested this hypothesis in both Guinea-Bissau and Denmark.MethodsWe conducted 2 studies: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…It has been reported that smallpox vaccination reduced susceptibility to unrelated infectious diseases,1 and in immunological in vitro studies, smallpox vaccination was associated with an up to fivefold reduction in C-C chemokine receptor 5 (CCR5) tropic HIV-1 replication 2. Based on vaccination scar readings in Guinea-Bissau and school health records in Denmark, we have shown that smallpox vaccination (and BCG) was associated with a lower risk of HIV-1 3. The adjusted OR for HIV-1 infection was 0.52 (95% CI 0.32 to 0.84) for women and 0.77 (95% CI 0.48 to 1.24) for men.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…It has been reported that smallpox vaccination reduced susceptibility to unrelated infectious diseases,1 and in immunological in vitro studies, smallpox vaccination was associated with an up to fivefold reduction in C-C chemokine receptor 5 (CCR5) tropic HIV-1 replication 2. Based on vaccination scar readings in Guinea-Bissau and school health records in Denmark, we have shown that smallpox vaccination (and BCG) was associated with a lower risk of HIV-1 3. The adjusted OR for HIV-1 infection was 0.52 (95% CI 0.32 to 0.84) for women and 0.77 (95% CI 0.48 to 1.24) for men.…”
Section: Introductionmentioning
confidence: 78%
“…Estimated smallpox vaccination scar prevalence in different age groups for each sequential HIV survey. Based on data from Bissau, Guinea-Bissau, previously published 6. The estimation for the age group ≥35 in 2016 was changed to ≥45 to ensure a steady smallpox vaccination coverage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies from Guinea-Bissau and Denmark show that individuals vaccinated against smallpox and/or Bacille-Calmette-Guérin (BCG) had a reduced risk of HIV-1 infection compared with non-vaccinated individuals [ 11 ]. This effect tended to be stronger in women, suggesting a gender-specific effect as seen for other vaccines.…”
Section: Introductionmentioning
confidence: 99%